Does non-steroidal anti-inflammatory (NSAID) ibuprofen induce antioxidant stress and endocrine disruption in mussel Mytilus galloprovincialis? - Gonzalez-Rey, Maria (2020)
Ibuprofen (IBU) is one of the most sold over-the-counter non-steroidal anti-inflammatory drugs (NSAID) and widely detected in the aquatic ecosystems. Nevertheless, the information regarding IBU effects in biota is still sparse. The goal of this study was to assess IBU potential effect as oxidative stress and endocrine disruption inducer in mussel Mytilus galloprovincialis applying a battery of biomarkers. Over two weeks of exposure to IBU (250 ngL(-1)), superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR), phase II glutathione S-transferase (GST) activities and lipid peroxidation (LPO) levels were determined in the digestive gland and alkali-labile phosphates (ALP) were carried out in sex-differentiated mussels' gonads. The results confirm a transitory induction of antioxidant activities responses concomitant to lipid peroxide formation outline and an increase of ALP levels over time, particularly in exposed males which may lead to mussels' reproductive fitness impairment highlighting a higher impact of IBU as an endocrine disruptor than as a short-term reactive oxygen species (ROS)-generator.